Framing Perseteruan Gerakan Dakwah Khuruj Fi Sabilillah Jamaah Tabligh Temboro Magetan - Moh. Yusuf (Proceedings of Annual Conference for Muslim Scholars, 2017)
The movement of khuruj fi sabilillah (outreaching in the Godâ€™s path ) as the daâ€™wah model of Jamaâ€™ah Tabligh has faced many obstacles since its first occurence in Temboro,Magetan District. The obstacles have not posed only by the existing daâ€™wah communities, political structure also poses non-trivial challenges. Ultimately, the Daâ€™wah movement of khuruj fi sabilillah is able to build the character of Muslims in Temboro into a typical Islamic-Salafid Muslims through the daâ€™wah of khuruj fi sabilillah. This study uses framing theory as an analyzing tool in reading occasions, framing experinces into meaning and guiding collective actions. Jamaâ€™ahTabligh can foster Temboro peopleâ€™s interests in khuruj fi sabilillahusing the meaning conception it frames, that khuruj fi sabilillahis a manhaj of the â€œsalaf al-salihâ€ (salafi), a walking madrasah, and a daâ€™wah model ofâ€œwalisangaâ€ (nine guardians).